2020
DOI: 10.3389/fnmol.2020.00103
|View full text |Cite
|
Sign up to set email alerts
|

Methyltransferase 3 Mediated miRNA m6A Methylation Promotes Stress Granule Formation in the Early Stage of Acute Ischemic Stroke

Abstract: The modification of methyltransferase-like (METTL) enzymes plays important roles in various cellular responses by regulating microRNA expression. However, how m6A modification is involved in stress granule (SG) formation in the early stage of acute ischemic stroke by affecting the biogenesis processing of microRNAs remains unclear. Here, we established a middle cerebral artery occlusion (MCAO) model in rats and an oxygen-glucose deprivation/reperfusion (OGD/R) model in primary cortical neurons and PC12 cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 49 publications
5
62
0
Order By: Relevance
“…Further, miR-335 directly targeted the ROCK2 3 UTR to inhibit apoptosis in PC12 cells [104]. Interestingly, in ischemic cortices of MCAO rats, METTL3, m6A, and miR-335 were up-regulated at 0 h after reperfusion but significantly down-regulated at 24 h after reperfusion [104]. This was similar in PC12 cells treated with oxygen-glucose deprivation/reperfusion (OGD/R) stimulation as an in vitro model of acute ischemic stroke [104].…”
Section: Membrane-less Compartmentsmentioning
confidence: 90%
See 2 more Smart Citations
“…Further, miR-335 directly targeted the ROCK2 3 UTR to inhibit apoptosis in PC12 cells [104]. Interestingly, in ischemic cortices of MCAO rats, METTL3, m6A, and miR-335 were up-regulated at 0 h after reperfusion but significantly down-regulated at 24 h after reperfusion [104]. This was similar in PC12 cells treated with oxygen-glucose deprivation/reperfusion (OGD/R) stimulation as an in vitro model of acute ischemic stroke [104].…”
Section: Membrane-less Compartmentsmentioning
confidence: 90%
“…Interestingly, in ischemic cortices of MCAO rats, METTL3, m6A, and miR-335 were up-regulated at 0 h after reperfusion but significantly down-regulated at 24 h after reperfusion [104]. This was similar in PC12 cells treated with oxygen-glucose deprivation/reperfusion (OGD/R) stimulation as an in vitro model of acute ischemic stroke [104]. Furthermore, METTL3-mediated m6A modifications of pri-miR-335 promoted the mature miR-335 expression, enhancing SG formation and attenuating apoptosis in OGD/R stimulated PC12 cells.…”
Section: Membrane-less Compartmentsmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been reported that m6A levels in the cortex and hippocampus of Alzheimer's disease (AD) mice were notably higher than those in the control group and that m6A methylation genes were involved in the pathways associated with the occurrence of AD (Han et al, 2020). Si et al (2020) found that METTL3-mediated miRNA m6A methylation promotes stress granule formation and reduces the apoptosis of injury neurons in the early stage of acute IS. Furthermore, Wang et al (2020a,b) found that the expression levels of METTL3 and WTAP were reduced in the larger pathological tissue of cerebral AVMs.…”
Section: Discussionmentioning
confidence: 99%
“…Using the middle cerebral artery occlusion (MCAO) model of ischemic stroke in rats, Si and colleagues found that METTL3-mediated methylation promoted maturation of miR-355 which then promoted stress granule formation which was neuroprotective ( Si et al, 2020 ). A role for m 6 A readers as regulators of the brain response to stroke has also been proposed.…”
Section: A In Brain Disordersmentioning
confidence: 99%